A high-pressure-resistant electrolyte and a battery comprising the same
Patent Information
- Application Number
- CN202211430056.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-15
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-11-15
AI Technical Summary
[0003]针对目前的电解液在高电压下的充放电过程中六氟磷酸锂和碳酸酯类有机溶剂发生分解而功能受损,同时产生HF等对电极有腐蚀作用,降低电池的使用寿命等问题,本发明提供了一种耐高压型电解液及包括该电解液的电池,所述电解液中含有作为第一添加剂的胺基酸酐类化合物,所述第一添加剂可以提高电解液的氧化电势,有效对抗电池的高压过充,同时还能够有效吸收电解液中多余的水分和六氟磷酸锂分解产生的HF,抑制电解液中碳酸酯类有机溶剂的氧化分解,减少电极与电解液的腐蚀副反应,提高电极的界面稳定性,从而提升电池的循环寿命
[0040]本发明提供了一种耐高压型电解液及包括该电解液的电池。所述电解液中的第一添加剂选自胺基酸酐类化合物,所述胺基酸酐类化合物的分子有较大偶极矩,具有更高熔点和热稳定性,能够提高电极的界面稳定性,提升电池的循环寿命,具体地:所述胺基酸酐类化合物中的胺基官能团(R-N-)能够抑制F-的生成;酸酐官能团(-C(=O)-O-(O=)C-)能够吸收可能出现的水分子的同时中和六氟磷酸锂分解产生的HF,从而有效抑制电解液在高电压电位下的分解,提高电池的循环寿命。此外,胺基官能团和酸酐官能团均为吸电子基团,其具有高氧化电位,能够匹配高电压的正极活性物质,达到提高电池能量密度的效果。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0003944810980000021
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a high-voltage resistant electrolyte and a battery including the electrolyte. Background Technology
[0002] Lithium-ion batteries, as a new type of green high-energy rechargeable battery, have advantages such as high operating voltage, large specific capacity, and long cycle life, and are widely used in portable devices such as mobile phones and laptops. With the development of the electric vehicle industry, there are higher requirements for the energy density of lithium-ion batteries, and high voltage and high energy density are important development directions. Currently, most commercial electrolytes contain carbonate substances that are prone to decomposition reactions under high voltage (>4.5V), generating gases such as HF, which corrode the positive electrode active material and reduce the battery's charge and discharge efficiency, significantly reducing the cycle life of the positive electrode active material. Summary of the Invention
[0003] To address the problems of current electrolytes decomposing during high-voltage charging and discharging, resulting in functional impairment and the generation of HF which corrodes the electrodes and reduces battery life, this invention provides a high-voltage resistant electrolyte and a battery including the electrolyte. The electrolyte contains an amino acid anhydride compound as a first additive. This first additive increases the oxidation potential of the electrolyte, effectively counteracting high-voltage overcharging. It also effectively absorbs excess water and HF generated from the decomposition of lithium hexafluorophosphate, inhibits the oxidative decomposition of carbonate organic solvents in the electrolyte, reduces corrosion side reactions between the electrodes and the electrolyte, improves the interfacial stability of the electrodes, and thus enhances the cycle life of the battery.
[0004] The objective of this invention is achieved through the following technical solution:
[0005] An electrolyte comprising an organic solvent, an electrolyte salt, and a functional additive, wherein the functional additive comprises a first additive selected from amino anhydride compounds.
[0006] According to an embodiment of the present invention, the amino anhydride compound is an R-modified compound containing an amino group and an anhydride group, wherein R is selected from -CHO, -COOH, -B(OH)2, substituted or unsubstituted -C 1-12 Alkylene -COOH, substituted or unsubstituted -C 1-12 Alkylene -SO3H, substituted or unsubstituted -COOC 1-12 Alkyl, substituted or unsubstituted -COC 1-12 Alkyl, substituted or unsubstituted -S(O)2C 1-12 Alkyl, substituted or unsubstituted -S(O)2C6-12 aryl, substituted or unsubstituted -C 6-12 Aryl-SO3H, -Si(R1)(R2)(R3), substituted or unsubstituted C 2-12 alkenyl, substituted or unsubstituted C 6-12 Aryl; if substituted, the substituent is alkyl, cyano, or halogen; R1, R2, and R3 may be the same or different, and are independently selected from C1. 1-12 alkyl.
[0007] According to an embodiment of the present invention, the amino anhydride compound has the structural formula shown in Formula I:
[0008]
[0009] R is selected from -CHO, -COOH, -B(OH)2, substituted or unsubstituted -C 1-12 Alkylene -COOH, substituted or unsubstituted -C 1-12 Alkylene -SO3H, substituted or unsubstituted -COOC 1-12 Alkyl, substituted or unsubstituted -COC 1-12 Alkyl, substituted or unsubstituted -S(O)2C 1-12 Alkyl, substituted or unsubstituted -S(O)2C 6-12 aryl, substituted or unsubstituted -C 6-12 Aryl-SO3H, -Si(R1)(R2)(R3), substituted or unsubstituted C 2-12 alkenyl, substituted or unsubstituted C 6-12 Aryl; if substituted, the substituent is alkyl, cyano, or halogen; R1, R2, and R3 may be the same or different, and are independently selected from C1. 1-12 alkyl.
[0010] According to embodiments of the present invention, R is selected from -CHO, -COOH, -B(OH)2, substituted or unsubstituted -C 1-6 Alkylene -COOH, substituted or unsubstituted -C 1-6 Alkylene -SO3H, substituted or unsubstituted -C 6-10 Aryl-SO3H, substituted or unsubstituted -C(O)2C 1-6 Alkyl, substituted or unsubstituted -COC 1-6 Alkyl, substituted or unsubstituted -S(O)2C 1-6 Alkyl, substituted or unsubstituted -S(O)2C 6-10 Aryl, -Si(R1)(R2)(R3), substituted or unsubstituted C 2-6 alkenyl, substituted or unsubstituted C 6-10 Aryl; if substituted, the substituent is C. 1-6Alkyl, cyano, halogen; R1, R2, R3 may be the same or different, and are independently selected from C. 1-6 alkyl.
[0011] According to embodiments of the present invention, R is selected from -CHO, -COOH, -B(OH)2, substituted or unsubstituted -C 1-3 Alkylene -COOH, substituted or unsubstituted -C 1-3 Alkylene -SO3H, substituted or unsubstituted -C 6-8 Aryl-SO3H, substituted or unsubstituted -C(O)2C 1-3 Alkyl, substituted or unsubstituted -COC 1-3 Alkyl, substituted or unsubstituted -S(O)2C 1-3 Alkyl, substituted or unsubstituted -S(O)2C 6-8 Aryl, -Si(R1)(R2)(R3), substituted or unsubstituted C 2-3 alkenyl, substituted or unsubstituted C 6-8 Aryl; if substituted, the substituent is C. 1-3 Alkyl, cyano, halogen; R1, R2, R3 may be the same or different, and are independently selected from C. 1-3 alkyl.
[0012] According to embodiments of the present invention, R is selected from -CHO, -COOH, -B(OH)2, substituted or unsubstituted -C 1-3 Alkylene -COOH, substituted or unsubstituted -C 1-3 Alkylene -SO3H, benzenesulfonic acid group, substituted or unsubstituted -C(O)2C 1-3 Alkyl, substituted or unsubstituted -COC 1-3 Alkyl, substituted or unsubstituted -S(O)2C 1-3 Alkyl, benzenesulfonyl, trimethylsilyl, substituted or unsubstituted C 2-3 alkenyl, substituted or unsubstituted C 6-8 Aryl; if substituted, the substituent is C. 1-3 Alkyl, cyano, halogen.
[0013] According to an embodiment of the present invention, the amino anhydride compound has the structural formulas shown in formulas A1 to A4:
[0014]
[0015]
[0016] According to an embodiment of the present invention, the weight of the first additive is 0.1wt% to 5.0wt% of the total weight of the electrolyte, preferably 0.5wt% to 3wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.2wt%, 1.3wt%, 1.5wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.8wt%, 3wt%, 3.3wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, or 5wt%.
[0017] According to an embodiment of the present invention, the electrolyte salt is selected from lithium electrolyte salts, and the lithium electrolyte salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorosulfonylimide.
[0018] According to an embodiment of the present invention, the weight of the electrolyte salt is 11wt% to 18wt% of the total weight of the electrolyte, for example, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt% or 18wt%.
[0019] According to an embodiment of the present invention, the organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate.
[0020] According to an embodiment of the present invention, the functional additive further includes a second additive, wherein the second additive is selected from at least one of the following: adioxonil (ADN), 1,3,6-hexanetrionitrile (HTCN), succinic anhydride, glyceryl trionitrile, fluoroethylene carbonate (FEC), 1,3-propanesulfonyl lactone (PS), 1,3-propenesulfonyl lactone, lithium difluorooxalate borate, lithium difluorophosphate, and lithium difluorodioxalate phosphate.
[0021] According to an embodiment of the present invention, the weight of the second additive is 1 wt% to 15 wt% of the total weight of the electrolyte, for example, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, or 15 wt%.
[0022] According to an embodiment of the present invention, the electrolyte is used in a battery, preferably in a lithium-ion battery.
[0023] The present invention also provides a battery comprising the electrolyte described above.
[0024] According to an embodiment of the present invention, the battery further includes a positive electrode sheet containing a positive electrode active material, a negative electrode sheet containing a negative electrode active material, and a separator.
[0025] According to an embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active material layer coated on one or both surfaces of the positive current collector, wherein the positive active material layer includes a positive active material, a conductive agent, and a binder.
[0026] According to an embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one or both surfaces of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder.
[0027] According to an embodiment of the present invention, the mass percentage of each component in the positive electrode active material layer is: 80-99.8 wt% positive electrode active material, 0.1-10 wt% conductive agent, and 0.1-10 wt% binder.
[0028] Preferably, the mass percentage of each component in the positive electrode active material layer is: 90-99.6 wt% positive electrode active material, 0.2-5 wt% conductive agent, and 0.2-5 wt% binder.
[0029] According to an embodiment of the present invention, the mass percentage of each component in the negative electrode active material layer is: 80-99.8 wt% negative electrode active material, 0.1-10 wt% conductive agent, and 0.1-10 wt% binder.
[0030] Preferably, the mass percentage of each component in the negative electrode active material layer is: 90-99.6 wt% negative electrode active material, 0.2-5 wt% conductive agent, and 0.2-5 wt% binder.
[0031] According to an embodiment of the present invention, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder, and carbon fiber.
[0032] According to an embodiment of the present invention, the adhesive is selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.
[0033] According to an embodiment of the present invention, the negative electrode active material includes carbon-based negative electrode materials and / or silicon-based negative electrode materials.
[0034] According to an embodiment of the present invention, the silicon-based anode material is selected from nano-silicon and silicon-oxygen anode materials (SiO2). x(0<x<2)) or at least one of silicon-carbon anode materials.
[0035] According to an embodiment of the present invention, the carbon-based anode material is selected from at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0036] According to an embodiment of the present invention, the mass ratio of the silicon-based anode material to the carbon-based anode material in the anode active material is 9:1 to 1:9, for example, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or 9:1.
[0037] According to an embodiment of the present invention, the cathode active material is selected from one or more of lithium cobalt oxide, lithium manganate, lithium iron phosphate, and ternary materials.
[0038] According to an embodiment of the present invention, the charging cutoff voltage of the battery is greater than or equal to 4.5V, preferably 4.5V to 4.8V.
[0039] Beneficial effects of the present invention:
[0040] The present invention provides a high-voltage resistant electrolyte and a battery comprising the electrolyte. The first additive in the electrolyte is selected from amino acid anhydride compounds. The molecules of the amino acid anhydride compounds have a large dipole moment, higher melting point and thermal stability, which can improve the interfacial stability of the electrode and enhance the cycle life of the battery. Specifically: the amino functional group (R-N-) in the amino acid anhydride compounds can inhibit the generation of F-; the acid anhydride functional group (-C(=O)-O-(O=)C-) can absorb possible water molecules and neutralize HF generated by the decomposition of lithium hexafluorophosphate at the same time, thereby effectively inhibiting the decomposition of the electrolyte at high voltage potential and improving the cycle life of the battery. In addition, both the amino functional group and the acid anhydride functional group are electron-withdrawing groups, which have high oxidation potential, can match the high-voltage cathode active material, and achieve the effect of improving the energy density of the battery. Detailed Description of the Embodiments
[0041] The present invention also provides the preparation method of the first additive as described above, and the method comprises the following steps:
[0042] 1) In terms of molar ratio, bis(2-chloroethyl)amine hydrochloride (CAS: 821-48-7): potassium hydroxide = 1:1. Under heating and stirring conditions, a potassium hydroxide solution with a concentration of 0.1 to 0.5 mol / L is gradually added dropwise to bis(2-chloroethyl)amine hydrochloride, and the reaction is fully carried out for 1 to 5 h. Then copper is added as a catalyst, manganese dioxide is added as an oxidant, the temperature is controlled at 60 to 100°C, the stirring rate is 300 r / min, and the solid phase is filtered off to obtain solution A;
[0043] 2) According to the volume ratio, solution A: copper hydroxide solution with a concentration of 0.01~0.05mol / L = 1:1, reflux reaction at 80~120℃ for 2~6h, filter off the solid phase, and purify by rotary evaporation to obtain solution B;
[0044] 3) According to the volume ratio, solution B: water-removing agent tetrahydronaphthalene: catalyst sodium dihydrogen phosphate = 100:30:1, reflux reaction for 6-12 hours, temperature controlled at 50-80℃, to obtain solution C;
[0045] 4) Solution C and a salt solution containing the R group are refluxed at 100-150°C for 3-8 hours to dehydrate, and purified by rotary evaporation to obtain the first additive, wherein the definition of R is as described above.
[0046] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0047] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0048] In the description of this invention, it should be noted that the terms "first," "second," etc., are used for descriptive purposes only and are not intended to indicate or imply relative importance.
[0049] The first additive with the structure of formula A1 used in the following examples was prepared by the following method:
[0050] Di(2-chloroethyl)amine hydrochloride and potassium hydroxide were mixed at a molar ratio of 1:1. Specifically, 0.1 mol / L potassium hydroxide aqueous solution was gradually added dropwise to the di(2-chloroethyl)amine hydrochloride while heating and stirring. Then, 1% copper and 3% manganese dioxide were added according to the total mass of the mixture. The temperature was controlled at 65℃ and the stirring rate was 300 r / min. The mixture was allowed to react for 5 hours. The mixture was then filtered and the filtrate was collected.
[0051] The filtrate was mixed with freshly prepared 0.05 mol / L copper hydroxide aqueous solution at a volume ratio of 1:1, and the mixture was refluxed at 85 °C for 6 h. The resulting mixture was then filtered, and the filtrate was collected.
[0052] After purifying the filtrate, it was mixed with tetrahydronaphthalene and sodium dihydrogen phosphate at a volume ratio of 100:30:1 and refluxed at 60°C for 10 h. Finally, it was refluxed with sodium benzenesulfonate at 120°C for 4 h to dehydrate and purified by rotary evaporation to obtain the first additive with the structure of formula A1.
[0053] Example 1
[0054] The method for preparing the electrolyte includes the following steps:
[0055] Ethylene carbonate, propylene carbonate, and dimethyl carbonate are mixed in a mass ratio of 1:1:1 to form an electrolyte solvent. 12 wt% of lithium hexafluorophosphate is dissolved in the solvent, and then 1.5 wt% of the first additive with the structure of formula A1 above and 2.5 wt% of 1,3-propenesulfonate lactone are added and mixed to obtain the electrolyte.
[0056] The method for preparing a lithium-ion battery includes the following steps:
[0057] Positive electrode preparation: The ratio of the positive electrode main material lithium cobalt oxide, the binder polyvinylidene fluoride, and the conductive agent acetylene black is 95%:2.5%:2.5%. An oily slurry is prepared using N-methylpyrrolidone (NMP) solution and finally coated on the surface of aluminum foil to form a positive electrode.
[0058] The negative electrode uses a lithium metal negative electrode.
[0059] The above-mentioned positive electrode, negative electrode, electrolyte, and PP / PE / PP three-layer separator were assembled into a CR2032 coin cell and subjected to 0.5C cycle tests at cutoff voltages of 3.0–4.5V, 3.0–4.6V, and 3.0–4.7V, respectively.
[0060] Specifically, the button batteries prepared above were tested at a temperature of 25°C, with the lower limit of the voltage range set at 3.0V and the upper limits at 4.5V, 4.6V, and 4.7V respectively. First, rate performance tests were conducted, with a charging rate of 0.1C and discharge rates of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C respectively. Then, cycle performance tests were conducted at a charge / discharge rate of 0.5C and voltage ranges of 3.0V–4.5V, 3.0V–4.6V, and 3.0V–4.7V.
[0061] Comparative Example 1
[0062] Electrolytes and lithium-ion batteries were prepared according to the process of Example 1, except that the first additive of the structure of Formula A1 was not added to the electrolyte, and the batteries were tested under the same conditions.
[0063] Example 2
[0064] The method for preparing the electrolyte includes the following steps:
[0065] Diethyl carbonate, methyl ethyl carbonate, and propylene carbonate are mixed in a mass ratio of 1:1:1 to form an electrolyte solvent. 15 wt% of lithium hexafluorophosphate is dissolved in the solvent, and then 3.5 wt% of the first additive with the structure of formula A1 above and 1.5 wt% of 1,3-propenesulfonyl lactone are added and mixed to obtain the electrolyte.
[0066] The positive electrode sheet of the battery was prepared according to Example 1, except that the negative electrode sheet was prepared as follows: the ratio of the negative electrode main material artificial graphite, the binder sodium carboxymethyl cellulose, and the conductive agent carbon nanotubes was 95%:2%:3%. Deionized water was used to make an aqueous slurry, which was then coated on the surface of copper foil to form the negative electrode sheet.
[0067] The positive and negative electrodes and the separator are arranged in a sandwich-like structure and wound into an 18650 cylindrical steel-cased battery. Finally, the electrolyte of this embodiment is injected. 1C charge-discharge cycles are performed at cutoff voltages of 3.0–4.5V, 3.0–4.55V, and 3.0–4.6V, respectively.
[0068] Specifically, the 18650 cylindrical steel-cased battery prepared above was tested at a temperature of 25°C. The lower limit of the voltage range was set at 3.0V, and the upper limits were set at 4.5V, 4.55V, and 4.6V respectively. First, rate performance testing was conducted, with a charging rate of 0.1C and discharge rates of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C respectively. Then, cycle performance testing was conducted under conditions of a charge / discharge rate of 1C and voltage ranges of 3.0V–4.5V, 3.0V–4.55V, and 3.0V–4.6V.
[0069] Comparative Example 2
[0070] Electrolyte and lithium-ion battery were prepared according to the process of Example 2, except that the first additive of the structure of Formula A1 was not added to the electrolyte, and the battery was tested under the same conditions.
[0071] Table 1. Performance test results of the batteries in the examples and comparative examples.
[0072]
[0073] Test results show that the lithium-ion battery with the electrolyte additives described in this embodiment of the invention has an effective improvement in cycle performance, and the improvement is even more significant at higher voltage systems.
[0074] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A battery, the battery comprising an electrolyte, characterized in that, The electrolyte comprises an organic solvent, an electrolyte salt, and a functional additive, wherein the functional additive comprises a first additive and a second additive, the first additive being selected from amino anhydride compounds having the structural formula shown in Formula I: Equation I R is selected from -S(O)2C 6-12 Aryl; The weight of the first additive is 1.5wt% to 3.5wt% of the total weight of the electrolyte; The second additive is selected from 1,3-propenesulfonyl lactone; The weight of the second additive is 1 wt% to 5 wt% of the total weight of the electrolyte; The charging voltage range of the battery is 3.0 to 4.7V.
2. The battery according to claim 1, characterized in that, R is selected from -S(O)2C 6-10 Aryl.
3. The battery according to claim 2, characterized in that, R is selected from -S(O)2C 6-8 Aryl.
4. The battery according to claim 3, characterized in that, The amino anhydride compound has the structural formula shown in formula A1: A1。
